2014
DOI: 10.1177/1471301214529783
|View full text |Cite
|
Sign up to set email alerts
|

Crucial dimensions constituting dignity experience in persons living with dementia

Abstract: Dignity is seen as an essential need, fundamental right, and inherent quality of each human being. There is however, a need for increased knowledge on crucial dimensions constituting dignity experience in persons living with dementia. This study explored personal dimensions of life which persons with dementia perceived crucial for experiencing dignity in their daily lives. Based on the findings of eight empirical sub-dimensions, three main dimensions crucial for constituting dignity experience, were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 28 publications
0
43
0
1
Order By: Relevance
“…Thirty‐seven citations claim to be hermeneutic and generally follow the method as it was intended (Söderhamn, Dale, & Söderhamn, ; Thorkildsen, Eriksson, & Råholm, ). Among the hermeneutic studies, however, Tranvåg, Petersen, and Nåden () use a combination of our method with that of Zimmer (). The study itself, although identified as hermeneutic, is somewhat muddled in its approach.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty‐seven citations claim to be hermeneutic and generally follow the method as it was intended (Söderhamn, Dale, & Söderhamn, ; Thorkildsen, Eriksson, & Råholm, ). Among the hermeneutic studies, however, Tranvåg, Petersen, and Nåden () use a combination of our method with that of Zimmer (). The study itself, although identified as hermeneutic, is somewhat muddled in its approach.…”
Section: Discussionmentioning
confidence: 99%
“…Participants also wanted to highlight their ability to be self-reliant and talked about areas of their life they were proud of such as school, careers or travel (Karlsson et al 2014). These findings are reinforced by Tranvag et al (2016) who also explored the personal dimensions of life that people with dementia perceived as important. Appreciating meaningful work and activities that enriched life in their past still seemed crucial even after the onset of dementia.…”
Section: Value Of Life Story Work For Patientsmentioning
confidence: 99%
“…It has also highlighted that challenges exist to ensure it can be implemented successfully and illuminated some best practice guidelines that should be considered. In particular, it has emphasised key areas to focus on during the gathering of life story work, including childhood memories, significant relationships, work, hobbies and other activities that the person enjoyed or was proud of and the moral issues of importance to them (Karlsson et al 2014, Tranvag et al 2016. Where possible it is beneficial to collaborate on the process with the person who has dementia, the family and care staff in a sensitive and supportive way, appreciating that it may evoke emotional experiences and respecting that it may not be for everyone.…”
Section: Now What?mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, people with early-onset memory disorders and their families face slightly different challenges from those who are older at the time of onset [11][12][13][14] . Previous studies concerning the subjective experiences of PMDs focus on their challenges, coping strategies [15][16][17][18] , the diagnosis' impact on their selfhood and identity [11,[19][20][21] , subjective reality [22,23] and dignity [24,25] . Issues relevant to family members' experiences that have been studied include changes in relations as well as caregivers' challenges, well-being, burden and coping mechanisms [8,[26][27][28][29] .…”
mentioning
confidence: 99%